Looking for a place for Sonification: Sons de Silício and the Buzu installation (Per Musi, 2021)
This paper discusses the concept of sonification aplied to the Sons de Silício exhibition and more specifically to the design of Buzu, an audiovisual installation that generates an auditory image of the São Paulo bus transportation system. Buzu makes perceptible information of both the system’s planning and behavior during a particular week in October 2017. The work is an artistic outcome of the InterSCity project, an inter‐institutional research initiative concerning the Future Internet and the Smart Cities. Along with the discussion of the Buzu creative process we will examine mining and processing strategies related to the sonification of big data, data‐to‐sound mapping methods, auditory structure for displaying the material and the public exhibition of the work in the context of an artistic event.